P253 Local anaesthetic thoracoscopy services in the uk. (December 2018) - de Fonseka, D; Bhatnagar, R; Maskell, N
Abstract : Background: Local anaesthetic thoracoscopy (LAT) is an important procedure in the management pathway of patients with pleural effusions, particularly those with suspected malignancy. The last survey evaluating the use and development of LAT services in the UK was over a decade ago. We performed a survey of LAT practices in the UK to explore procedural preferences and variations in practice. Method: The survey was designed and conducted by the Academic Respiratory Unit at North Bristol NHS Trust. The online survey was cascaded via regional pleural specialists to sites performing LAT. One response per site was accepted. Results: 37 responses were received from England, Scotland and Wales. 95% of responding centres consider LAT to be their preferred method for investigating an undiagnosed pleural effusion. 92% of the centres had a dedicated pleural procedure list, with frequency varying from twice per week to ad-hoc (figure 1). Most centres have regular access to a dedicated list and a designated area to perform LAT. 97% of the centres have at least 2 trained thoracoscopists. A majority (76%) of centres prefer to routinely admit patients overnight following a LAT. All except one centre practised a single port entry method, while rigid thoracoscopy was the most popular technique used (31/37, 84%). Some variation in practice is seen with patient preparation pre-procedure and medication use. Other procedures such as insertion of indwelling pleural catheters and adhesiolysis are not uncommon to be undertaken at the time of LAT. 10/37 (27%) of centres had access to on-site thoracic surgical support. The availability of local standardised operating procedures (SOP) for potential complications was uncommon. Conclusions: This survey represents the most up to date and complete account of any nation's LAT practice. Overall the results are comparable, excepting some minor variations in patient preparation pre-procedure. We hope that this survey functions as an information resource for centres developing a LAT service or for those considering expansion.